Perceived organizational politics and getting satisfied or dissatisfied with job (2007)
The study investigated perception of organizational politics and how it affects workers’ job satisfaction. Two levels of organizational politics were considered, namely, group level and organizational level. Two hundred and three (203) employees participated in the study which employed ex post facto design. Scales used in the study include 9-item modified perception of organizational politics scale originally developed by Ferris and Kacmar (1992), 6-item perception of group politics and 10-item job satisfaction scale by Adanijo (1987). Independent t-tests were used to test the study’s three hypotheses. It was found that perception of politics at the management or organizational level affected employees' job satisfaction significantly. There was no significant difference in the way male and female employees perceived politics at the organizational/level. Similarly, male and female employees did not report job satisfaction differently. The findings point to the fact that organizational policies need to always recognize the need for eliminating intense politics in the work place to boost workers’ job satisfaction and productivity. Findings also point to the need for harmonizing goals of employees and their organizations.